The moderating role of organizational culture on the relationship between emotional intelligence and transformational leadership - Al Issa, Hussein-Elhakim (2017)
The purpose of this empirical research is to examine the interrelated influences among emotional intelligence, organizational culture, and transformational leadership. In particular, the current study investigated the effect of emotional intelligence as a predictor of transformational leadership. The potential moderating effects of organizational culture on the relationships between the dimensions of emotional intelligence and transformational leadership were also examined. Data was collected from a sample of 333 academic leaders in 18 public universities in peninsular Malaysia. Transformational leadership was measured by using the Multifactor Leadership Questionnaire (MLQ-5x Short), emotional intelligence, using the Wong and Law Emotional Intelligence Scale (WLEIS), and organizational culture, using the Organizational Culture Assessment Instrument (OCAI). Structural equation modeling by means of partial least square bootstrapping resampling was used for hypotheses testing. Methodological improvements were made to overcome some of the challenges identified by past research that examined emotional intelligence and leadership. These concerns included common method variance, smaller sample sizes, relatively lower construct reliability, and researching sole organizations. The statistical results revealed a significantly positive relationship between transformational leadership and three of the independent variables, namely, self-emotion appraisal, others emotional appraisal, and use of emotion. The study of organizational culture as a moderator between the dimensions of emotional intelligence and transformational leadership was also unprecedented. Generally, organizational culture played an important role in moderating this relationship. However, the moderating effect of organizational culture as a whole construct, and clan and hierarchy type cultures were found significant only on the relationship between regulation of emotion and transformational leadership while adhocracy type culture negatively moderated the relationship between others emotional appraisal and transformational leadership. The results of this study contribute to the present pool of knowledge about the interrelationships of emotional intelligence, organizational culture and transformational leadership, showing that the power of leaders’ emotional intelligence on transformational leadership is expressed through a third moderating variable, organizational culture. Theoretically, the study is hopeful to further understandings of the predictive power of emotional intelligence dimensions on transformational leadership, as well as contribute insights as to the conditional effect of organizational culture on the relationship. The findings of the study will also help practitioners improve the selection and development of leaders.